Website Pemasaran Digital Sebagai Media Konten dan Sarana Promosi Produk Unggulan Usaha Mahasiswa - Rayie Tariaranie Wiraguna; Naswan Suharsono; Titis Shinta Dhewi (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2023)
Numerous challenges arise concomitant with the rapid advancement of technology through digital marketing models that have been deployed by several small enterprises to rival comparable products. The transition to the digital market owing to the Industrial Revolution and the COVID-19 pandemic poses both threats and opportunities for technology-driven multinational corporations and micro and small enterprises. Nevertheless, only a few entrepreneurs have been able to capitalise on these prospects. In 2022, the significance of non-traditional media in science and technology for developing new product marketing capabilities that are autonomous, adaptable, and environmentally attuned is becoming more evident. It is crucial to establish entrepreneurship programmes tailored to the needs and requirements of 25 UMK students as per their respective groups and technical disciplines. Programmes should be customised to suit the capabilities, requirements, and preparedness of each department to facilitate the development of an entrepreneurial culture. An attempt has been made to establish synergy bridges using a specific approach. This approach can be implemented progressively and steadily for a particular cohort of skilled businesses or simultaneously for a variety of target groups. An organised campaign is required to foster an entrepreneurial culture through education and training of the target groups. The Programme for the Application of Science and Technology in Business (P2M) will be executed by LPM to enhance the entrepreneurial aptitude of 25 UMK students. This project intends to develop the business skills of the participants while maintaining objectivity in its evaluations. The use of simple sentences and causal connections facilitates the comprehension and logical coherence of the text. Consistent formatting and a conventional structure have been employed, while a high register and precise vocabulary have been utilized to maintain a balanced, value-neutral tone. Grammatical correctness has been ensured through careful editing. The Programme for the Application of Science and Technology in Business (P2M) will be executed by LPM to enhance the entrepreneurial aptitude of 25 UMK students.